The Preference of The Sub-Urban Society in Choosing The Satellite Area of Denpasar City as a Residential - Wira Raditya, Agung Angga; Sueca, Ngakan Putu; Wirawibawa, Ida Bagus Gde (Journal of A Sustainable Global South; Vol 5 No 1 (2021): February 2021, 2021)
Villages suburb area around the border with the city of Denpasar is one of the area that’s also effected by the economic growth in Denpasar city. The area was settled by people due to sub-urban residential land in Denpasar increasingly difficult to reach and limited, especially   those located in the center of Denpasar City. It makes people prefer living in the satellite city of Denpasar. The area included in the district of Gianyar, Badung, and Tabanan regency. This study aims to determine the preference that are considered sub-urban communities to choose satellite settlements in Denpasar. This study uses the positivist approach with merging between qualitative and quantitative case study. The research result obtained five factors are considered sub-urban communities to choose satellite settlements in Denpasar, among others: accessibility, availability of shopping facilities, environmental conditions, availability of electricity, and the pierce of land/house. Thus, accessibility becomes a major factors in the selection of the sub-urban residential location in the satellite city of Denpasar. Index Terms — preference, settlement, sub-urban, sattellite settlement